Perbandingan Kinerja Flokulasi Bioflokulan dari Pati Talas (Colocasia Esculenta L. Schoott) Termodifikasi dengan Pati Singkong (Manihot Utilissima) Termodifikasi Menggunakan Metode Pencangkokan (Grafting) - Resqi Dwi Oktaviani; Novitasari Novitasari; Mujtahid Kaavessina (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2016)
Flocculation is one of processes to obtain clean water. Starch-graft-polyacrylamide (St-g-PAM) is a copolymer flocculant. This flocculant is synthesized by the “grafting to” method. This study aims to determine the effects of initiator concentration ratio, the terminator concentration and the termination time towards the obtained flocculant performance. Polymerization was carried out in a glass reactor equipped with a stirrer and isothermal conditions. The resulting products were analyzed by FT-IR. The analysis shows the existence bonds of starch and acrylamide. The presence of these groups proves that St-g-PAM was formed. The effect of initiator concentration ratio showed that the performance bioflocculant from mocaf more effective than bioflocculant from modified taro strach, with the higher change value is 76,19 %. Meanwhile, the effect of the terminatorconcentration and the termination timeshowed that the performance bioflocculant from modified taro strach more effective than mocaf, the higher change valuesare 68,57% and 71,76%, respectively.